Nomenclatural notes and typification of two names in Mallotus (Kamala tree) (Euphorbiaceae) - Shinde, Santosh Shyam; Bramhadande, Sneha Pradeep; Dalavi, Jagdish Vishnu; Kumar, Ettickal Sukumaran Santhosh; Shendage, Shankar Maloji (Phytotaxa, 2025)
N/A